Synthesis of Some New 6-Methylimid azo [2,1-b] thiazole-5-carbohydrazide Derivatives and their Antimicrobial Activities - Ur, Füsun; Cesur, Nesrin; Birteksöz, Seher; Ötük, Gülten (Arzneimittelforschung, 2004)
In this study, 14 new compounds having 6-methyl-N2-(alkylidene/cycloalkylidene) imidazo [2,1-b] thiazole-5-carbohydrazide (3a-g), 3-[[(6-methylimid-azo [2,1-b] thiazole- 5 -yl)carbonyl] amino]-4-thiazolidinone (4a-d) and 4-[[(6methyl-imidazo [2,1-b] thiazole-5-yl) carbonyl] amino]-1-thia-4-azaspiro[4.4]nonan/[4.5]dec-an-3-one (4e-g) structures were synthesized. The structures of the compounds were elucidated by UV, IR, 1H-NMR, 13C-NMR, 1H-13C-COSY, mass spectra and elemental analysis. All compounds synthesized were tested for antimicrobial activity against Staphylococcus aureus ATCC 6538, Staphylococcus epidermidis ATCC 12228, Escherichia coli ATCC 8739, Klebsiella pneumoniae ATCC 4352, Pseudomonas aeruginosa ATCC 1539, Salmonella thypi, Shigella flexneri, Proteus mirabilis ATCC 14153, Candida albicans ATCC 10231 and Mycobacterium tuberculosis H37Rv. Only 4d and 4f demonstrated antimicrobial activity against S. epidermidis ATCC 12228 (MIC: 19.5 µg/ml and 39 µg/ml, respectively).
Keywords: Hydrazide-hydrazones; Imidazo[2,1-b]thiazoles, antimicrobial activity, synthesis; 1-Thia-4-azaspiro[4.4]nonan-3-one, antimicrobial activity, synthesis; 1-Thia-4-azaspiro[4.5]decan-3-ones, antimicrobial activity, synthesis; 4-Thiazolidinones, antimicrobial activity, synthesis